An overview of the green building's criteria: Non residential new construction - Bahaudin, Ahmad Yusni; Mohamed Elias, Ezanee; Nadarajan, Sivasegaran; Romli, Ruslan; Zainudin, Nizamuddin; Mohd Saifudin, Adam (2012)
Designers and clients alike are now emphasising on how to make their buildings green.Currently a lot of green councils worldwide are dealing with innovative ways to implement energy efficient new buildings.They have adopted various criteria and rating systems in an endeavour to classify buildings that contribute to environment sustainability, efficiency and users health.The aim of the paper is to present an overview of the criteria adopted by selected green building councils.This paper discusses five of the rating systems available in terms of similarity and contrast and proposes a new framework based on the project life cycle for the development green building criteria.Criteria during the construction phase of the building is certainly lacking such as pollution control in terms of C02 emission, dust, and other pollutants.